Influence Of Intellectual Capital, Income Diversification on Firm Value Of Companies With Profitability Mediation: Indonesian Banking - Windie Yustyarani (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
This study aims to examine and analyze the effect of intellectual capital and income diversification on firm value mediated by profitability. This study uses secondary data from annual reports on banks listed on the Indonesia Stock Exchange in 2013-2018. There are 30 banking samples in this study based on established criteria (purposive sampling). Data analysis using the WarpPLS 6.0 program. The results showed that intellectual capital had a positive effect on profitability and on firm value, income diversification had a negative effect on profitability, while it was found to have no effect on firm value, profitability had a positive effect on firm value, intellectual capital had an indirect effect on firm value mediated by profitabilit with partial mediation, while mediation is not supported by the indirect effect of Income Diversification on Firm Value.